Cultivating Culturally Relevant and Sustaining Pedagogy through Field Experiences: Discourses of Elementary Preservice Teachers of Color. Issue 4 (1st October 2020) - Maddamsetti, Jihea
ABSTRACT: This study uses Bakhtin's theory of dialogism to examine how two preservice teachers of Color conceptualized and implemented culturally relevant and sustaining pedagogy (CR/SP) during their practicum. The participants' development and practice of CR/SP were contingent on their lived experiences, appropriation of CR/SP, dialogic negotiations with multiple stakeholders, and critical engagement with circulating authoritative discourses during their fieldwork. By considering how preservice teachers of Color dialogically engage with CR/SP in the field, teacher educators can design field experiences that better prepare culturally responsive preservice teachers of Color.